The one world schoolhouse : education reimagined - Khan, Salman, 1976- (New York, NY : Twelve, 2012)
"A free, world-class education for anyone, anywhere: this is the goal of the Khan Academy, a passion project that grew from an ex-hedge funder's online tutoring sessions with his niece, who was struggling with algebra, into a worldwide phenomenon. Today, millions have viewed and subscribed to the Khan Academy's YouTube videos, which have expanded to encompass nearly every conceivable subject. Like all great innovators, Sal Khan established himself as an outsider, with no teaching background to tie him to broken models. And his breakthrough idea has become his life's passion. Schools seek his advice about connecting to students in a digital age, and people of all ages and backgrounds flock to the site to utilize this new approach to learning. In The One World Schoolhouse, Khan will present his remarkable story, as well as his vision for the future of education. More than just a solution, his book serves as a call for free, universal, global education, and an explanation of how his simple - yet revolutionary - method can help achieve this inspiring goal"--
""The founder of the Khan Academy -- the world's most popular free online learning site -- tells the story of his school's astonishing success, and shares his revolutionary vision for the future of education." --Provided by the publisher.
Introduction: A free, world-class education for anyone, anywhere -- Pt. I: Learning to teach : Teaching Nadia ; No-frills videos ; Focusing on the content ; Mastery learning ; How education happens ; Filling in the gaps -- Pt. II: The broken model : Questioning customs ; The Prussian model ; Swiss cheese learning ; Tests and testing ; Tracking creativity ; Homework ; Flipping the classroom ; The economics of schooling -- Pt. III: Into the real world : Theory versus practice ;The Khan Academy software ; The leap to a real classroom ; Fun and games ; Taking the plunge ; The Los Altos experiment ; Education for all ages -- Pt. IV: The one world schoolhouse : Embracing uncertainty ; My background as a student ; The spirit of the one room schoolhouse ; Teaching as a team sport ; Ordered chaos is a good thing ; Redefining summer ; The future of transcripts ; Serving the underserved ; The future of credentials ; What college could be like -- Conclusion: Making time for creativity.
Includes bibliographical references.
Keywords: Internet in education; Education and globalization; Self-culture.